US imbalances: the role of technology and policy - Rudolfs Bems; Luca Dedola; Frank Smets (European Central Bank (ECB), 2007)
This paper investigates the role of three likely factors in driving the steady deterioration of the US external balance: US technology developments, changes in the US government fiscal position and the Fed's monetary policy. Estimating several Vector Autoregressions on US data over the period 1982:2 to 2005:4 we identify five structural shocks: a multi-factor productivity shock; an investment-specific technology shock; a monetary policy shock; and a fiscal revenue and spending shock. Together these shocks can account for the deterioration and subsequent reversal of the trade balance in the 1980s. Productivity improvements and fiscal and monetary policy easing also play an important role in the increase of the external deficit since 2000, but these structural shocks can not explain why the trade balance deteriorated in the second half of the 1990s.
Keywords: F3; F4; 330; global imbalances; open economy; VARs; Außenwirtschaftliches Gleichgewicht; Technischer Fortschritt; Öffentliche Schulden; Geldpolitik; Offene Volkswirtschaft; USA